The Influence of Entrepreneurial Characteristic on Business Performance - Solihat, Asri; Amelia, Renita; Hamdani, Nizar Alam; Permana, Intan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study discusses the analysis of the effect of entrepreneurial characteristic on business performance. Researchers used quantitative methods with data collection techniques using questionnaires. Data quality analysis techniques used validity test methods, reliability tests, while hypothesis testing used simple linear regression analysis and t test. Based on the results of research conducted, entrepreneurial characteristic has a significant effect on business performance. That way the results of this research can help companies and entrepreneurs to implement the business that is being occupied, and can make it easier for future researchers to find the latest references if they have the same variables so that the research can be helped to be more perfect